Life style and oral health of Brazilian adolescents from rural settlements - Moimaz, Suzely Adas Saliba [UNESP]; Leão, Milene Moreira; dos Santos, Luis Felipe Pupim [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Tânia Adas [UNESP] (My University, 2018)
Objective: Verify the behavior, habits and the oral health of Brazilian adolescents from rural settlements considering the access inequity to odontological services. Methods: In this cross-sectional epidemiological study, 179 adolescents. were interviewed using the Global School-based Student Health Survey instrument. Data were collected on caries index, periodontal health, dental services accessibility, diet and hygiene habits, and body mass index. Results: 53.3% of the respondents had consulted a dentist in the last year. High-caloric food consumption (p =.0465) and toothbrushing only once a day (p =.0172) were associated with gingival bleeding, which was related to unsatisfactory oral health (p =.0082). The presence of caries was associated with insufficient toothbrushing (p =.0001), which was related to chewing difficulty (p =.0098) and being embarrassed to smile (p <.0001). Conclusion: Inequity of access to odontological services resulted in high caries index and gingivitis. Obesity and low-frequency toothbrushing increased the risks of these diseases. The difficulty in access culminated in the aggravation of the dental affections, damaging the chew and the social life of the adolescents. Public Health Policies to prioritize socially excluded populations area a necessity, as well as Health Promotion strategies to cope oral problems.
Estilo de vida e saúde oral de adolescentes brasileiros residentes em assentamentos rurais
Keywords: Adolescent behavior; Oral health; Public health; Rural population